Hydrogen Bonding-Mediated Enhancement of Bioinspired Electrochemical Nitrogen Reduction on Cu2-xS Catalysts - Kim, Min-Cheol; Nam, Hyunji; Choi, Jihyun; Kim, Hee Soo; Lee, Hong Woo; Kim, Donghun; Kong, Jimin; Han, Sang Soo; Lee, Seung Yong; Park, Hyun S. (AMER CHEMICAL SOC, 2020)
The electrochemical nitrogen reduction reaction (NRR) has been regarded as a promising alternative to the conventional Haber-Bosh process for NH3 synthesis. Inspired by the Fe-Mo-S cofactor in the enzyme nitrogenase, metal sulfide catalysts, mostly Fe- or Mo-based sulfides, have recently received great interest. Here, we propose Cu2-xS (0 <= x < 1) as an efficient NRR electrocatalyst. Electrochemical tests at room temperature and atmospheric pressure reveal that Cu1.81S achieves a high NH3 yield of 2.19 mu mol h(-1) cm(-2) along with a Faradaic efficiency of 14.1% at -0.1 V versus reversible hydrogen electrode in an aqueous electrolyte. According to our first-principles calculations, the superior NRR properties originate from the threefold-coordinate Cu sites in Cu1.81S. These sites enable N-H center dot center dot center dot S hydrogen bonding during N2Hy adsorption and stabilize the intermediates on the Cu2-xS surfaces, leading to a significant decrease in the overpotential limit for the NRR. Moreover, the threefold sites not only provide a bioinspired NRR pathway similar to that of nitrogenase but also enable both distal and alternating pathways, increasing the efficiency for the NRR. This study presents an attractive electrocatalyst for the NRR and opens an alternative route to explore chalcogenides and halides as NRR catalysts where the hydrogen-bonding mediation can similarly operate.
Keywords: AMMONIA-SYNTHESIS; ELECTROREDUCTION; ELECTROCATALYST; HYBRID